Makna Hukuman Cambuk dalam QS. An-Nur Ayat 2 dan 4: Studi Komparatif Tafsir Sayyid Qutb dan Tafsir Al-Misbah - Asiska Nadia Hasibuan; Sori Monang (CV Global Research Publication, 2026)
The punishment of flogging in Surah An-Nur verses 2 and 4 is often understood merely as a physical sanction, even though these verses contain broader legal, moral, and social dimensions. This study aims to analyze and compare the interpretation of Sayyid Qutb in Fī Ẓilāl al-Qur’ān and M. Quraish Shihab in Tafsir Al-Misbah regarding the meaning of flogging in Surah An-Nur verses 2 and 4. This research uses a qualitative method based on library research with a comparative (muqāran) approach. The primary data are taken from Fī Ẓilāl al-Qur’ān and Tafsir Al-Misbah, while secondary data are obtained from books, journal articles, and relevant academic literature. The results show that both commentators agree that flogging is intended to protect public morality, individual honor, and social order. However, Sayyid Qutb emphasizes the enforcement of divine law and the sovereignty of God’s law (ḥākimiyyah), while M. Quraish Shihab emphasizes contextual understanding, the objectives of Islamic law (maqāṣid al-syarī‘ah), justice, and human dignity. This study concludes that flogging in the Qur’an should not be understood solely as physical punishment, but as a legal instrument aimed at preserving honor, morality, and public welfare.